Child rearing practices of Filipino urban mothers relationship to children's cognitive development - Umali-Razon, Perpetua G. (1981)
The study investigated the child rearing patterns of Filipino urban mothers and the relationship of child rearing practices to the cogntive development of children. It also determined the relationship of family structure, mother's work status, socio-economic status of the family, sex and birth order of the child to child rearing and children's cognitive performance. One hundred fifty mother-child pairs were used as subjects. The child-rearing practices of each mother were investigated through an interview schedule. Three child-rearing dimensions were applied; love-hostility, autonomy-control, and cognitive growth. The cognitive performance of the child was determined through a test of 10 items on cognitive tasks which included conservations, classification and seriation.
The t-test showed that Filipino urban mothers are more loving than hostile but are more controlling than permissive. They were found to rate high in providing for the cognitive growth of their children. The chi-square test showed that except for birth order all the other variables studied (i.e., family structures, etc.) do not relate to child-rearing in each of the three dimensions.
The analysis of variance showed no significant differences in the cognitive performance of children grouped by sex, family structure, work status of mother, and socio-economic status. Birth order came out as the only variable associated with differences in cognitive performance of children. The differences are in favor of the youngest followed by the oldest and followed by the middle.
Includes bibliographical references (pages 14-15).